Methods for considering equality and equity implications in horizon scanning for medicines and healthcare innovations: a scoping review - Chizoba Oparah; Tafadzwa Patience Kunonga; Claire Eastaugh; Gill Norman (Journal of Health Equity)
Anticipating and addressing inequalities and/or inequities in access to and outcomes from emerging health technologies is essential for responsive and just health systems. Horizon scanning presents a strategic opportunity to integrate equity and/or equality considerations early in the innovation lifecycle. This scoping review identified and critically synthesised methods for embedding these considerations into healthcare-focused horizon scanning, with particular attention to how acceptability, polypharmacy, and multiple long-term conditions (MLTC) are addressed. Following JBI methodological guidance, we systematically searched MEDLINE, Embase, ProQuest, and WHO Global Index Medicus up to 24 May 2024 for studies reporting methodological approaches to incorporating equity or equality in horizon scanning. Primary outcomes examined definitions and operationalisation of these concepts, while secondary outcomes assessed how acceptability, polypharmacy, and MLTC were treated. Of 951 records screened, three studies met inclusion criteria. These studies used diverse foresight methodologies across different health system contexts. Two adopted an explicit equity lens, addressing structural determinants of health and targeting interventions to population-specific vulnerabilities; one employed a narrower equality framing focused on access without attending to systemic disadvantage. The treatment of acceptability, polypharmacy, and MLTC was limited and inconsistent, highlighting a lack of standardisation in current horizon scanning practices concerning complex, intersecting health needs. Overall, the integration of equity and equality into horizon scanning remains conceptually and practically inconsistent. Future approaches should clearly distinguish between these concepts and use frameworks that uncover structural barriers and support inclusive innovation. Strengthening this dimension of horizon scanning is essential for advancing health justice and improving system resilience.